Paranoia eaudiobook - Patterson, James (Michael Bennett, 2025)
NYPD Detective Michael Bennett will stop at nothing to protect family: his wife, his kids—and his fellow officers—in the latest psychological thriller from bestselling author James Patterson. At every death scene, Bennett says a prayer over the victim. But recently, too many of the departed have been fellow cops. "I want you to look at these deaths on special assignment," NYPD Inspector Celeste Cantor says. "Report only to me." Bennett excels as a solo investigator. But he's chasing a killer who feeds on isolation... and paranoia.